Penerapan Metode Drill untuk Meningkatkan Motivasi Belajar Siswa pada Pelajaran Matematika di Kelas IV SDN 039 Air Terbit Kabupaten Kampar - Suci Amalia; Wismanto Wismanto; Sakban Sakban (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
The drill method is serious repetitive activities do the same thing to strengthen or hone skills and make it permanent. The aim of this research is 1) To find out how to apply the drill method in mathematics lessons in class 4 at SDN 039 Air Terbit, 2) To find out whether the drill method is able to overcome students’ difficulties in understanding mathematics lessons, 3) To increase students’ learning motivation by applying the drill method in mathematics lessons in class 4 at SDN 039 Air Terbit. The method in this research uses classroom action research.. PTK is an approach to improving education through change by encouraging teachers to think about ttheir own practice so that they are critical of these actors an teachers want to change them. The results of this research are that students’ learning motivation is increasing. This can be seen from the results of the initial test. Learning engagement increased from 30% to 45% at the end of cycle 1 test and increased again at the end of cycle 2 test to 80%. So from the test result above it can be concluded that learning using the drill method can increase students’ learning motivation in mathematics lessons, the material on operations for calculating fractions can be seen from the increased learning result, so student motivation also increases.